Pelatihan Penggunaan Multimedia Guna Meningkatkan Minat Belajar Pada Sekolah Advent Anggrek - Alexander, Allan D; Warta, Joni (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
The Anggrek Adventist School was established in 1985 and currently consists of 2 educational units, namely the Anggrek Adventist Elementary School and the Anggrek Adventist Junior High School, this school is located at Jl. Orchid no. 17 Koja Tanjung Priok, North Jakarta and has a total of 152 students. Most of the students come from families with low socioeconomic status. In several studies, the socioeconomic conditions of parents affect students' learning requests where the low economic and social conditions of parents will make it difficult for students to develop themselves compared to the condition of parents of students whose socio-economic conditions are better because they are able to support the educational needs of their children so that can motivate students to study well. The use of audio-visual media can increase interest in learning by using audio-visual media, students will experience interesting things from the previous situation, based on research that has been done showing that the use of audio-visual (multimedia) can increase student interest in learning and for those services activities to This community will focus on training the use of multimedia to increase interest in learning in Orchid Adventist School students, and the multimedia application that will be used is wordwall where the use of this application can increase student participation in learning and it is hoped that with increasing student participation in the learning process, interest will also increase. students to take lessons.